The effect of Cissus quadrangularis L. on delaying bone loss in postmenopausal women with osteopenia: A randomized placebo-controlled trial - Benjawan S. (2023)
Background: Osteopenia refers to bone density that is not normal but also not as low as that noted in osteoporosis. Osteopenia leads to osteoporosis and increases the risk of fractures. Current research is focused on agents that will prevent or slow the progression of bone loss. On the basis of published evidence, Cissus quadrangularis (CQ) might potentially provide a novel natural treatment for osteopenia. Purpose: To determine the effect of 24 weeks of consecutive treatment with CQ on delaying bone loss and safety in postmenopausal women (PMW) with osteopenia. Methods: This study is a randomized, placebo-controlled trial. Here, 134 enrolled PMW with osteopenia (> 40 years and having no period for 1–10 years) received CQ at 1.2 (CQ1.2) or 1.6 g/day (CQ1.6) or placebo. The %change in bone mineral density (BMD) at the lumbar spine (L1–L4), femoral neck, and total hip served as the primary outcome. The %change in bone turnover markers (BTMs), including C-terminal telopeptide of type 1 collagen (CTX) and procollagen type 1 amino-terminal propeptide (P1NP), was the secondary outcome. These outcomes were compared between the CQ vs. placebo group at weeks 12 and 24. The least significant change (LSC) was used to monitor clinical changes. The adverse events (AE) were monitored. Results: A total of 108 participants completed this study. The %BMD changes in the CQ-treated groups did not differ at any site after 24 weeks compared to the placebo. Statistically significant differences were detected in CQ1.6 at the lumbar spine (0.011 ± 0.025 g/cm2, p = 0.008) and CQ1.2 at the femoral neck (–0.015 ± 0.036 g/cm2, p = 0.024) compared to baseline, but these changes did not exceed the LSC. Reduced bone remodeling activity was detected in both CQ-treated groups. Compared to the placebo, the %P1NP change was significantly reduced in CQ1.6 (–2.46 ± 26.05%; p < 0.01) at week 12 and in CQ1.2 (–3.36 ± 29.47%; p < 0.01) and CQ1.6 (–9.95 ± 22.22%; p < 0.01) at week 24. These results correlated with the within-group comparison, which showed a continuously significant increase in both BTMs in the placebo group. However, a stable CTX and a significant reduction in P1NP (p < 0.05) were detected in both CQ-treated groups. This reduction exceeded the LSC of P1NP. The incidence of adverse events did not differ among the three groups. Conclusion: This is the first clinical report that showed a promising effect on delaying bone loss of orally administration of CQ for 24 weeks, as indicated by a slower bone remodeling process via a reduction in BTMs. However, no change in BMD was observed.